Agricultural Product Safety: Vertical Farm Project Concept - et. al., Zhaina Zhanaykyzy TOLEGEN, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, we propose the concept of developing a modular cell for the construction of a vertical truss, which is attached to the bulk of residential buildings. The main idea is to introduce a modular cell in the Kazakhstan market for the development of urban farming. Vertical farms made up of modular cells are designed for growing organic agricultural products in urban environments. It is proposed to place vertical trusses in the blind, functionally undeveloped ends of residential buildings.The relevance of the production of organic agricultural products is outlined in the strategic development plan of the country, as one of the important areas responsible for the growth of the well-being of the people and the health of the younger generation. One of the well-known methods of organizing organic agriculture in urban settings is the use of vertical farms. Vertical trusses are widely used in the form of separate equipment-racks located inside the room. There are design proposals for vertical trusses in the form of separate independent buildings. The vertical truss proposed in this study consists of modular cells, which allows you to apply different compositional solutions. This cell has the ability to be arranged in different ways and adapt to any area. Vertical trusses will be built into the blind ends of residential buildings. After all, it is known that the area under the blind ends of 5-9-storey residential buildings do not find their high-quality use and very often create unfavorable, to some extent criminally dangerous sections of the city. According to the latest statistics of criminology, most of the crimes committed in the city occur in areas with blind ends of residential buildings. The height and total area of the vertical trusses will depend on the height of the residential buildings and on the overall aesthetic design of the spatial organization of the environment. The competitive advantage of the developed modular cell is the versatility of its application, mobility, as well as the interdisciplinary basis of the combined areas-architecture, design, agriculture, healthcare, construction, etc.The expected result is the qualitative development of urban farming, which can become a new market niche for the production of organic products. Urban farming can become new jobs for the residents of the houses in which vertical farms are built. And also, one of the directions in solving the problems of creating conditions for the growth of the well-being of the people and the health of the younger generation.